Path Discovery And Selection For Energy Efficient Routing With Transmit Power Control In MANET - Bhanumathi, V.; Dhanasekaran, R. (Malaysian Journal of Computer Science, 2013)
Main aim of the work is to design an energy efficient routing mechanism based on Dynamic Source Routing (DSR). In order to achieve energy efficient reliable transmission, routing here is divided into two parts. One is to discover the path based on Received Signal Strength (RSS) and residual energy and the other is to select based on minimum energy consumption. By eliminating the nodes that has low RSS value in transmission, path breakages can be avoided. Discovering the path based on residual energy results in the reduction of node failure. Selecting the path that consumes less energy extends the network lifetime. The prediction of RSS for path discovery under mobility will make the transmission reliable. The proposed work called Path Discovery and Selection for Energy Efficient Routing (PDSEER) is designed in such a way that when DSR starts the route discovery after checking its route cache , the required transmit power is set first inorder to save energy. Then RSS of the RREQ and node's remaining energy is validated for deciding whether a node can forward the RREQ or not. The data is transmitted after selecting the path that consumes minimum energy. Simulation results are compared for overhead, packet delivery ratio, energy consumption, number of path breakages and delay. The analysis reveals that the proposed system is energy efficient compared to basic DSR, PAMP, SSBR and MTPCR.